Statistical knowledge of biology education students in Malang - Diani Fatmawati; Mohannad Alobid; Indah Permatasari; Solikhah Solikhah; Ahmad Fauzi (Jurnal Biolokus: Jurnal Penelitian Pendidikan Biologi dan Biologi, 2022)
Statistical knowledge is a basic competency which must be possessed by Biology Education students before conducting research. Unfortunately, Statistics is often considered a difficult subject by biology students. The purpose of this survey research was to explore the statistical knowledge of Biology Education students. A total of 40 students in the Universitas Muhammadiyah Malang were involved in this research. The data were collected using a questionnaire containing 12 statements. Descriptive statistics was used to analyze the research data. The results showed that the mean score of students' statistical knowledge was 77.92 ± 17.96; meanwhile, 52.5% of students’ knowledge was categorized as good. In addition, the accuracy of student answers on several items reached over 90%, even though there were also items in which the answers were only 50% accurate. Therefore, innovation in Statistics lecture needs to be carried out to optimize the empowerment of statistical knowledge for Biology Education students.